2021
DOI: 10.3390/polym13234118
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Functionalization: Covalent and Non-Covalent Interactions and Their Characterization

Abstract: Chitosan (CS) is a natural biopolymer that has gained great interest in many research fields due to its promising biocompatibility, biodegradability, and favorable mechanical properties. The versatility of this low-cost polymer allows for a variety of chemical modifications via covalent conjugation and non-covalent interactions, which are designed to further improve the properties of interest. This review aims at presenting the broad range of functionalization strategies reported over the last five years to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 176 publications
(336 reference statements)
0
20
0
Order By: Relevance
“…Previous research has demonstrated the antimicrobial properties and antiproliferative activity of CS-TiO 2 NPs [ 49 , 50 ] and also discovered a CS-TiO 2 NPs-based food preservation film and methyl orange dye degrading CS-TiO 2 composites [ 51 ]. The CS-TiO 2 nanoparticles may be used for industrial wastewater treatment because the functionalized CS possesses adsorbent properties such as mesoporous properties, which enhance CS-TiO 2 interactions, nano-size, and surface area [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the antimicrobial properties and antiproliferative activity of CS-TiO 2 NPs [ 49 , 50 ] and also discovered a CS-TiO 2 NPs-based food preservation film and methyl orange dye degrading CS-TiO 2 composites [ 51 ]. The CS-TiO 2 nanoparticles may be used for industrial wastewater treatment because the functionalized CS possesses adsorbent properties such as mesoporous properties, which enhance CS-TiO 2 interactions, nano-size, and surface area [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the non-covalent interaction of molecules is the primary approach to be considered to increase the mechanical properties of CS/PVA blends. According to Nicolle et al [ 45 ], chitosan-based materials can be modified in their characteristics via non-covalent attachment by combining with small molecules, proteins, and polymers. Under this technique, the characteristics of chitosan depend on non-covalent interactions, such as hydrogen bonds, ionic bonds, and chelation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intensity of the peaks has increased in the MIP; this increase in the intensity could be attributed to ionic bonding taking place in the material. 35 A covalent bonding can be ruled out as the synthetic route selected does not favor the formation of amides in the structure. The implications of such a structure will have implications in the extraction process and reusability.…”
Section: Characterization Of the Materialmentioning
confidence: 99%